PERAN PERSEPSI DUKUNGAN ORGANISASI SEBAGAI MODERATOR DALAM PENGARUH BEBAN KERJA DIGITAL TERHADAP TINGKAT QUIET QUITTING KARYAWAN - Sutarno, Sutarno; Azzahra, Fatimah; Rahmadhan, Muhammad Rizky (Jendela Inovasi Daerah, 2026)
The phenomenon of quiet quitting has increasingly emerged in various workplaces, particularly among young employees. Although employees continue to perform their formal job duties, their emotional engagement with work tends to decline. This condition is closely associated with the increasing digital workload, such as continuous notifications, unlimited online meetings, and the blurring boundaries between work and personal life. This study aims to examine the effect of digital workload on quiet quitting and to analyze the moderating role of perceived organizational support in this relationship. This study employed a quantitative approach using multiple linear regression analysis. The sample consisted of 250 employees aged 20–40 years working in sectors with a high dependence on digital technology. Data were collected through an online questionnaire measuring digital workload, quiet quitting, and perceived organizational support. The results indicate that digital workload has a positive and significant effect on quiet quitting. Furthermore, perceived organizational support has a negative effect on quiet quitting and is proven to moderate the relationship between digital workload and quiet quitting, thereby mitigating the negative impact of digital workload on employee engagement. These findings highlight the important role of perceived organizational support in maintaining employee engagement under high digital work pressure and in preventing the escalation of quiet quitting.